Radiation resistance of composite scintillators containing grains of Y₂SiO₅:Ce or Y₃Al₅O₁₂:Ce obtained by solid-phase synthesis - Boyarintsev, A.Yu.; Galunov, N.Z.; Levchuk, L.G.; Martynenko, E.V.; Nepokupnaya, T.A.; Onufriyev, Yu.D.; Popov, V.F.; Voloshyna, O.V. (Functional Materials, 2018)
The paper focuses on the study of radiation resistance of composite scintillators containing the grains of Y₂SiO₅:Ce or Y₃Al₅O₁₂:Ce. The paper compares the results obtained for composite scintillators when the grains were made in two ways: (i) by grinding the ingots of the above substances those were obtained by solid phase synthesis, and (ii) by grinding the single crystals growing from the melt. The samples were irradiated by 8.3 MeV beam electrons (at the dose rate 1500 Mrad/h). The paper presents the photoluminescence spectra and values of the relative detection efficiency of beta-radiation of the scintillators measured before and after irradiation by accumulated dose D of 30 and 50 Mrad.